أثر إدارة معرفة الزبون على تحقيق الابتكار في عناصر المزيج التسويقي الإضافية - دراسة حالة مديرية التجارة لولاية سطيف- - لدرع, نعيمة; رقاد, صليحة (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة لمعرفة أثر إدارة معرفة الزبون (ببعديها) وهما المعرفة الصريحة والمعرفة الضمنية على تحقيق الابتكار في عناصر المزيج التسويقي الإضافية وأثرها على الابتكار في كل عنصر من عناصره المتمثلة في (الدليل المادي، الأفراد والعمليات). حيث تم توزيع 80 استبانة على موظفي مديرية التجارة لولاية سطيف جميعها صالحة للتحليل الإحصائي. توصلت الدراسة لوجود أثر ذو دلالة إحصائية لإدارة معرفة الزبون على تحقيق الابتكار في عناصر المزيج التسويقي الإضافية وأثر ذو دلالة إحصائية لبعدي إدارة معرفة الزبون على تحقيق الابتكار في (الدليل المادي، الأفراد والعمليات) بمديرية التجارة لولاية سطيف. This study aims to know the impact of customer knowledge management (with its two dimensions), which are explicit knowledge and implicit knowledge on achieving innovation in the additional marketing mix elements and its impact on innovation in each One of its elements (physical evidence, individuals and processes) .Where 80 questionnaires were distributed to the employees of the Directorate of Commerce of the wilaya of Setif, all valid for statistical analysis. the study found a statistically significant effect of customer knowledge management on achieving innovation in the additional marketing mix elements and a statistically significant effect of the two dimensions of customer knowledge management on achieving innovation in (physical evidence, individuals and processes) in the Directorate of Commerce of the wilaya of Setif
The impact of customer knowledge management on achieving innovation in additional marketing mix elements -Case study of the Directorate of Commerce of the wilaya of Setif
مقال
Keywords: إدارة معرفة الزبون ; المعرفة الصريحة ; المعرفة الضمنية ; الابتكار في الدليل المادي ; الابتكار في الأفراد ; الابتكار في العمليات; customer knowledge management ; explicit knowledge ; tacit knowledge ; innovation in physical evidence ; innovation in individuals ; innovation in processes